KLASIFIKASI KARAKTER BERDASARKAN PENILAIAN SIKAP SOSIAL TEMAN SEJAWAT PADA KURIKULUM 2013 MEMANFAATKAN NAIVE BAYES - Imron Rosadi (Jurnal Teknika, 2018)
This  aim  of  this  researh  is  to  classify  an  assessment  sentence  from  students,  then  classified  to  produce  an information. Classification is used to determine the character of   each student so that teachers have no difficulty in  assessing  the  social  character  of  the  student,  based  on  asesment  orientation  On  Kurikulum  2013.  This research  is empasize  to  processing opinion for the  students  to evaluate their friend in  SMA Negeri 1 Ngimbang Lamongan,  and  the  opinion  to  evaluate  each  student  will  classified  into  6  social  attitudes  that  is  Honest, Discipline,  Responsibility,  Pay  Attention  (mutual  cooperation,  tolerance),  well  manered  and  selsf  confidence, this  research  is  divide  into  2  phase  that is the  process  to produce  training data  (dataset) and the process to classify  opinion (test data). Both off the process are to  at extracting the attributes and  object components which commented in every document and to decide  the classification social attitudes classfication for each student.On the system for this character clasification produce accuracy with the sucess rate from the result of the testing clasficataion use Algoritman Naive Bayes success rate of 72%, this approach paper I use of 80%, the succes rate of 72% because the use of the sentence for rating colleague had the rate of variants are quite low that affect the process off making the data that will be used to the system off the clasificaton of characterer